A construção de tesauros em contextos de complexidade cultural, social e política: uma proposta para Justiça de Transição - Pablo Gomes (2023)
This research intends to experiment on the construction of a thesaurus surrounded by questions of a cultural, social and, mainly, political nature. The identified research problem questions the inclusion of inclusive terminologies of the cultural, social and political context, expressed in the plurality of voices of the social actors who work in the Transitional Justice (TJ) area, in order to expand the representation of a thesaurus for this area. The general objective was to develop an approach for building a thesaurus to TJ that stresses the methods postulated in Information Science (IC) and includes terminologies that include the cultural, social and political context, expressed in the plurality of voices of the social actors who work in this area. The specific objectives included: i) elaborating, with other theoretical and methodological bases, a matrix for the construction of a thesaurus that fulfills the characteristic of hosting cultural, social and political issues; ii) specify the actors that make up the JT area; iii) recover and systematize TJ terminologies from the diverse voices that make up the area; iv) analyze the thesaurus as a result of the demand for different representations of TJ. The theoretical framework includes a discussion on the Social Organization of Knowledge, with discussions on thesauri as devices in Foucauldian logic and how these instruments of informational practice can fulfill a commitment to diversity and truth. It also includes an understanding of what Transitional Justice is and a journey through the Military Dictatorship (1964-1985) in Brazil. The methodology involves the participatory paradigm of the Social Sciences. This is a qualitative and interpretative research. The methodological procedures involve the construction of a thesaurus for TJ with Social Science methods and techniques and data collection for the construction process. The main technique used in the construction of the thesaurus was the Focus Group, promoting a displacement of the validation of terms/concepts from terminological materials to the actors of the democratic transition, and, in addition, bibliographical and documental research. The model chosen for the construction of the thesaurus abandons traditional models and guidelines, based on a positivist view. Data were analyzed using content analysis and discourse analysis. The first part of the analysis and discussion of the results comprised the construction process of a thesaurus prototype having the cultural warranty as the main element of validation of terms/concepts for terminological representation. In this way, the analysis and discussion started from the cultural warranty to treat the materials, intend the methods and identify the terms. The second part covered the discourse analysis on the thesaurus prototype. For this analysis, the following terms were selected: Military Dictatorship (1964), Military Dictatorial Regime, Justice and Desamnesty. The final considerations make notes about the research process, returning to the research problem and objectives. With this research, it was possible to verify that the change in the centrality of terminological materials for the actors of the transition made it possible to represent TJ with a commitment to the truth with the clarifications of the traumatic past.